Chicken beauty pageant - Amrit Kaur Jastol (2016)
This report highlights our journey to produce Chicken Beauty Pageant (hereinafter abbreviated as CBP), a documentary about the Serama chicken hobby in Malaysia and Indonesia. From conceptualization to postproduction, CBP underwent numerous changes in angle, treatment and style. This report aims to provide insight into the group’s filmmaking process and experience.